2009
DOI: 10.1093/chemse/bjp011
|View full text |Cite
|
Sign up to set email alerts
|

Retro-Nasal Aroma Release Depends on Both Subject and Product Differences: A Link to Food Intake Regulation?

Abstract: It is hypothesized that differences in the extent of retro-nasal aroma release during consumption may be 1 of the reasons that people vary in their satiation characteristics. Using real-time atmospheric pressure chemical ionization mass spectrometry (APcI-MS), in vivo retro-nasal aroma release was determined for 30 subjects consuming 9 different food products, varying in physical structure (i.e., [semi]liquid and solid food products). Additionally, for a subset of the subjects ad libitum food intake was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 26 publications
2
64
1
Order By: Relevance
“…The inter-individual specificity in odorant release profiles during consumption, as a function of individual eating patterns, has been confirmed in a recent study (Ruijschop, Burgering, Jacobs, & Boelrijk, 2009). It was shown that subjects with relatively high retronasal aroma release intensities for a (semi) liquid food product also appeared to have a relatively high retronasal aroma release for a solid food product.…”
Section: Chewing and Swallowing Patterns And Tongue Movementsmentioning
confidence: 55%
“…The inter-individual specificity in odorant release profiles during consumption, as a function of individual eating patterns, has been confirmed in a recent study (Ruijschop, Burgering, Jacobs, & Boelrijk, 2009). It was shown that subjects with relatively high retronasal aroma release intensities for a (semi) liquid food product also appeared to have a relatively high retronasal aroma release for a solid food product.…”
Section: Chewing and Swallowing Patterns And Tongue Movementsmentioning
confidence: 55%
“…With the apple juice there is only a brief moment of sensory stimulation; the vast majority of the sugar and aroma molecules pass the oral/pharyngeal cavity without contact with the senses of smell and taste. The big difference in the duration of aroma ( = olfactory) stimulation between various liquid and solid foods was recently confirmed by Ruijschop et al (41) , who measured aroma molecules in the exhaled air during food consumption. The duration of aroma release was about ten times longer for mature cheese (solid) than for a strawberry-flavoured dairy liquid (41) .…”
Section: Sensory and Metabolic Signals Involved In Eating Behaviourmentioning
confidence: 69%
“…Similar inter-individual variability in aroma release profiles has been reported previously (Buettner et al, 2002;Pionnier et al, 2004); as such it may be a consequence of physiological differences in timing as well as in the performance of mastication and swallowing. In spite of this variability, subjects can be characterised according to the extent of aroma release, independent of the type of food (subjects who show a relative high aroma release when consuming a liquid/semi-liquid food product also show a relative high release for solid food products, Ruijschop et al, 2009). …”
Section: In Vivo Release Kineticsmentioning
confidence: 99%
“…Such studies have benefited substantially from the development of rapid and sensitive instrumental techniques, particularly Proton Transfer Reaction Mass Spectrometry (PTR-MS) (AprĂ©a, Biasioli, Gasperi, MĂ€rk, & Van Ruth, 2006;Boland, Delahunty, & Van Ruth, 2006;Mestres, Kieffer, & Buettner, 2006;Van Ruth, de Witte, & Uriarte, 2004) and Atmospheric Pressure Chemical Ionisation Mass Spectrometry (APCI-MS) (Gierczynski, LabourĂ©, SĂ©mon, & Guichard, 2007;Ovejero-Lopez, Haahr, Van den Berg, & Bredie, 2004). The effects of product structure result from a combination of physicochemical (entrapment of aroma compounds in the product structure and/or obstruction of their mass transport) and physiological phenomena (types of oral behaviour) (Buettner & Beauchamp, 2010;Buettner, Beer, Hannig, Settles, & Schieberle, 2002;Pionnier et al;Ruijschop, Burgering, Jacobs, & Boelrijk, 2009;Wright & Hills, 2003). In most cases, increasing product viscosity or firmness results in decreasing aroma release and perception (Baek, Linforth, Blake, & Taylor, 1999;Boland et al, 2006;Hansson, Giannouli, & Van Ruth, 2003), although some contradictory results have been reported (Hollowood, Linforth, & Taylor, 2002;Mestres et al, 2006;Weel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%